Amyloid Negative, Highly Tau Positive: Clinical Characterization of a Rare Biomarker Profile. (20th December 2022) - Windon, Charles; Iaccarino, Leonardo; Mundada, Nidhi S.; Apostolova, Liana G.; Carrillo, Maria C.; Dickerson, Brad C.; Grant, Harli E.; Miller, Bruce L.; Shankar, Ranjani; Soleimani‐Meigooni, David N.; Joie, Renaud La; Rabinovici, Gil D.; et al.
Abstract: Background: The majority of individuals with unambiguously positive tau biomarkers (T++) have positive amyloid biomarkers. Here we describe cases with clinical features associated with an unusual biomarker profile: very high tau PET binding and negative amyloid PET (A‐T++). Method: We searched the Longitudinal Early‐Onset Alzheimer's Disease (AD) Study, University of California San Francisco AD Research Center and the AD Neuroimaging Initiative cohorts on 09/01/2021 for participants with completed amyloid PET (Florbetapir, Florbetaben, Pittsburgh Compound B) and Tau PET (Flortaucipir (FTP)) scans and identified 1420 participants (mean age 69, 49.7% male). Using a pathology‐based, neocortical centiloid threshold of 24.4 (amyloid positivity) and a pre‐defined region of interest (Temporal MetaROI) standardized uptake value ratio (SUVR) > 1.27 threshold (tau positivity), we identified 64 amyloid negative, tau positive cases. An additional MetaROI FTP‐SUVR threshold > 2.0 (based on visual plot of data) was then applied to identify 7 A‐T++ cases (Figure 1). Result: Among A‐T++ individuals mean age was 66.2 (range 53.8 ‐ 77.1), 4/7 were female, mean years of education was 15 (range 12 ‐ 20), mean MMSE was 20 (range 14‐29), 3/7 were APOE e3/e4 and clinical phenotypes included amnestic and atypical AD phenotypes (Table 1). Mean neocortical centiloid value was 11.4 (range: ‐1.39 ‐ 17.11) among A‐T++ cases and 4/7 had centiloid values between 12.2 ‐ 24.4 (may be indicative of early positivity). Mean FTP SUVR was 2.28 (range 2.03 ‐ 2.63) (Table 2). All A‐T++ cases demonstrated FTP tracer binding within the middle temporal cortex, medial temporal structures, and posterior cingulate regions (Figure 2). Neuropathological data from 1 case (UCSF3) revealed frequent CERAD Neuritic Plaques, Thal Amyloid Plaque Phase 5, and Braak Neurofibrillary Degeneration Stage 6 (autopsy performed 1 year after amyloid PET). Conclusion: A‐T++ individuals were heterogeneous clinically but all displayed FTP tracer binding in AD‐signature regions. Four cases had amyloid centiloid values above 12.2 (threshold to detect moderate‐to‐frequent CERAD scores) but below 24.4 (threshold to detect intermediate‐to high Alzheimer's disease neuropathologic change (ADNC) levels). Pathological data available for 1 case revealed a high level of ADNC. False negative amyloid PET in A‐T++ individuals is an important consideration; future studies are needed.